Pendekatan-Pendekatan Dalam Mengembangkan Kurikulum Pendidikan Dasar - Musa’adatul Fithriyah (Universitas Islam Lamongan, 2017)
The curriculum is designed to achieve a dynamic education. It should be developed especially in keeping up with any scientific and technological development. The basic education curriculum is aimed at developing and designing a new curriculum in addition to changing, improving, implementing and even taking control of the basic curriculum. In regard with the curriculum development, it should be implemented through some systematic approaches to produce a better curriculum in accordance with the objectives of national education. The approaches of developing basic education curriculum are carried out by implementing appropriate strategies and methods by taking into account the systematic development steps to produce a better curriculum, especially that is in line with the basic education level. The use of an approach or orientation generally determines the form and pattern used by the curriculum. The approaches that could be used in the development of basic education curriculum are, among others: 1) the subjectmatter approach, 2) the integrative approach, 3) the centralized approach, 4) the decentralized approach, 5) the social reconstruction approach, 6) the technological approach, 7) the humanistic approach. Based on the study of several approaches used in the development of the Basic Education curriculum, it is expected that teachers could develop curriculum and produce a better curriculum especially the Basic Education curriculum to achieve the expected educational goals.Keywords: Approach, curriculum development, basic education